Algebraic expression #5

mathwannabe

Junior Member
Joined
Feb 20, 2012
Messages
122
Hello everyone :D

I have never worked on this type of problem before. I got the same answer that the book provides, but that book is proven to be evil and I don't trust it one bit x)

Here is the problem and how I did it (or not LOL):

1) \(\displaystyle \dfrac{a^{2n+1}-a^{2n-1}}{a^{n-1}+a^n}=\)

\(\displaystyle =\dfrac{a^{2n}a-a^{2n}a^{-1}}{a^na^{-1}+a^n}=\)

\(\displaystyle =\dfrac{a^{2n}(a-a^{-1})}{a^n(a^{-1}+1)}=\)

\(\displaystyle =\dfrac{a^n(a-a^{-1})}{a^{-1}+1}=\)

\(\displaystyle =\dfrac{a^n(a-\frac{1}{a})}{\frac{1}{a}+1}=\)

\(\displaystyle =\dfrac{a^n(\frac{a^2-1}{a})}{\frac{a+1}{a}}=\)

\(\displaystyle =a^n\dfrac{(a-1)(a+1)}{a}\times\dfrac{a}{a+1}=a^n(a-1)\)
 
Top